Nodular Lymphocyte-Predominant Hodgkin Lymphoma in Progressive Transformation of Germinal Centers - C. Eric Bailey; Francesca Jung; Benjamin Addicks; Olukemi A. Esan; Brian Kellermeyer (Case Reports in Otolaryngology)
Nodular lymphocyte-predominant Hodgkin lymphoma is an uncommon variant of Hodgkin lymphoma. Progressive transformation of germinal centers has been associated with and can develop prior to, concurrent with, or after the diagnosis of nodular lymphocyte-predominant Hodgkin lymphoma. We present a patient with a history of progressive transformation of germinal centers of the right parotid who presented 4 years later with ipsilateral parotid mass and cervical adenopathy. Knowledge of her previous diagnosis raised our concern for lymphoma, influenced our surgical management, and spared the patient additional surgery with risk of facial nerve injury inherent in revision parotidectomy.